Optimizing Project-Based Learning in Developing 21st Century Skills: A Future Education Perspective - Adam Mudinillah; Dedi Kuswandi; Erwin Erwin; Sugiarni Sugiarni; Winarno Winarno; Annajmi Annajmi; Sam Hermansah (Qubahan Academic Journal)
Many studies show that the effectiveness of project-based learning in the perspective of future education is influenced by 21st century skills. This can be a support to solve any problems faced by students in learning. Therefore, it is important for students to improve 21st century skills as a guide to equip themselves to prepare for the life to come. The purpose of this research is to optimize project-based learning in developing 21st century skills. Creating a new innovation in the perspective of increasingly sophisticated future education, helping students develop more complex and in-depth thinking skills so that it can provide an effective solution related to all forms of challenges that occur in the world of education. The method used in this research is quantitative method. The steps are to make statements related to tips for improving 21st century skills from the perspective of future education. Then formulated into a google form and filled in by middle and high school students. Then the data is collected and then inputted and processed using the spss application. The truth of the data can be proven by the statements made on the google form which are adjusted to the facts that occur in students. Results. Based on effective observation, it is found that 21st century skills play an important role in today's modern learning process. Skills that can equip every student to prepare themselves and realize all forms of life demands that change according to the times. The conclusion of this research is that teachers are advised to understand more about 21st century skills, in order to teach students how to adapt to increasing technological changes, so as to expand learning opportunities and enrich students' learning experiences through skills practiced by teachers.